Where’s My Money Go? / Puteri Nur Syuhadah Kamarol Ariffin ... [et al.] - Kamarol Ariffin, Puteri Nur Syuhadah; Abd. Aziz, Nurul Hanis; Roslan, Iffah Hanna; Mohd Tob, Nur Hanisah; Ab Hasan, Zunaidah (Universiti Teknologi MARA, Kedah, 2023)
“Where’s My Money Go?” is an application that is developed for university students. In this application, it consists of several tabs such as home, tips, records, financial analysis and profile. Saving money as a student isn't always easy student tend to overspend. One of the common money management mistakes that university students make is does not have a plan where to spend the money as they not determining "Wants vs. Needs". Thus, it is important to keep track of their spending as they have to carefully spend their money each month. Objective for this app is to setting up saving goals for student so they can understand and learn how spending wisely affects their financial success. The innovation that our group are working on is application which teach about how to manage saving and spending. Furthermore, we improvise this application by adding counseling sessions that provide “Q&A” to know about the user’s current life in aspects physical and mental health about problem of personal financial. This application also creates better graphics in the teaching aids that will help boost the mood of the user with cute animated stickers and photos. It will benefit society to better plan and manage actual saving and spending in daily. Also, they can learn and use the knowledge that they gain from the apps in their life. This product is easy to install and access. Besides, it has good security to protect user’s account by automatically log out after they do not use it.